Numerical study of fluid flow and temperature distributions in a data center. (December 2021) - Yang, Tien-Fu; Chen, Yu-Chun; Chen, Bo-Lin; Li, Chun-Han; Yan, Wei-Mon
Abstract: With the advent of 5th-generation mobile networks, the internal computing of data centers is very important. However, a server's calculations cause significant thermal problems. Therefore, this study focuses on the thermal analysis of a single rack in a data center. In this work, the airflow and temperature distributions in a single rack are examined numerically in detail. The computational fluid dynamics software is used to simulate the airflow field and temperature profile. The focus of the research is removal of heat from servers in the rack under different operating conditions and designs. The predicted results show that Case 2's size and 0.45 m of raised-floor depth would help to create a uniform airflow distribution at the same rate. Besides, the Return temperature index is used to evaluate the performance of data center. The results of Model 1 and 2 for three flow rate are presented and compared in details.